Empowering Faculty Excellence: How University Support, Commitment, and Digital Technology Drive Performance - Rafli, Muhammad; Lubis, Kartika Sari; Rony, Shofyan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
The objective of this study is to evaluate the effect of higher education institution support on lecturer performance, with commitment as a mediating variable and the function of digital technology as a moderator in the relationship between variables. One of the private universities in XXX Province's undergraduate economics study program served as the site for this investigation. A questionnaire survey with a sample of 269 respondents was the methodology employed. The SEM-PLS method was used to analyze the data. The findings demonstrated that instructor dedication is impacted by university assistance. In addition, university support also affects lecturer performance through mediation of commitment, and the relationship is further strengthened by the use of digital technology as a moderator. The implications of this study emphasize the importance for private universities in XXX Province to consider these factors in the management and development of human resources, especially lecturers, this study contributes both theoretically and practically to a deeper understanding of the factors that affect lecturers' commitment and performance, with the goal of improving the quality of education.